2013
DOI: 10.1007/s00586-013-3051-7
|View full text |Cite
|
Sign up to set email alerts
|

One-stage anterior debridement, bone grafting and posterior instrumentation vs. single posterior debridement, bone grafting, and instrumentation for the treatment of thoracic and lumbar spinal tuberculosis

Abstract: Anterior debridement and bone grafting with posterior instrumentation may not be the best choice for treating patients with spinal tuberculosis. Single posterior debridement/bone grafting/instrumentation for single-segment of thoracic or lumbar spine tuberculosis produced good clinical results, except in patients who had a psoas abscess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 27 publications
5
99
0
Order By: Relevance
“…After the technique was introduced, the Hong Kong operation became a popular method to treat spinal tuberculosis [8,15,16]. Taking into account the intense trauma, higher incidence of complications and instability of the spine from the anterior approach [17], more surgical methods paid attention to the treatment of spinal tuberculosis from the posterior approach within the last one to two decades [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…After the technique was introduced, the Hong Kong operation became a popular method to treat spinal tuberculosis [8,15,16]. Taking into account the intense trauma, higher incidence of complications and instability of the spine from the anterior approach [17], more surgical methods paid attention to the treatment of spinal tuberculosis from the posterior approach within the last one to two decades [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The summary of the meta-analysis for correction of angle after surgery is shown in Figure 4. The data of effect on correction of angle were available in all studies (24)(25)(26)(27) (Figure 6). It indicated that the posterior approach group spent less time in the hospital than the combined posterior and anterior approach group.…”
Section: Results Of Data Analysismentioning
confidence: 99%
“…All of the studies reported the data on fusion time and fusion rate of the grafting bone after surgery (24)(25)(26)(27). A total of 253 patients (group A, 129; group B, 124) were included to assess the overall effects of fusion time.…”
Section: Results Of Data Analysismentioning
confidence: 99%
See 2 more Smart Citations